Strategies for Preventing Election Violations by the Bantul Regency Election Supervisory Agency (Bawaslu) in the 2024 Bantul Regent and Deputy Regent Elections - Verdi Suryatama; Ane Permatasari (Journal of Governance and Social Policy, 2026)
This study aims to analyze the election violation prevention strategies implemented by the Bantul Regency Election Supervisory Agency (Bawaslu) in the 2024 Bantul Regent and Deputy Regent Elections based on Alfred D. Chandler's Organizational Strategy Theory (1962). The study uses a descriptive qualitative approach through interviews, observations, and documentation studies. The results show that Bawaslu implemented risk-based strategies through vulnerability mapping, organizational structure strengthening, clear division of tasks, inter-agency coordination, strengthening of participatory oversight, and planned resource allocation. However, the implementation of these strategies still faces obstacles in the form of limited human resources, low community participation, and complex local political dynamics. These findings contribute theoretically to the study of electoral organization strategies and have practical implications for strengthening policies to prevent violations in future regional elections at the local level in a sustainable manner.